dimedcom 2022
DOI: 10.35760/dimedcom.2022.v1i2.7421
|View full text |Cite
|
Sign up to set email alerts
|

Wedding Organizer Marketing Communication Strategy @NGANTENAN.YUK Through Instagram Social Media

Abstract: This study aims to determine the marketing communication strategy of Wedding Organizer @Ngantenan.Yuk through Instagram social media. With the Instagram social media Wedding Organizer @Ngantenan. Let's do marketing and promotion. Marketing and advancements made by Wedding Organizer @Ngantenan.Yuk are posting photos and videos of client weddings and information about weddings through Instagram. The research method used in this study is a qualitative descriptive method. Primary data is from information obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Therefore, it is suggested that the accounts created in this research were part of the student preferences. This percentage is very high when compared to data indicating that on Instagram, small accounts with less than 5,000 followers achieve an average reach of 8.43% in stories (12). Only some entertainment accounts reach 85% of views, and certain sports accounts have the highest following: 90% (13) At the level of the UCR, the Faculty outreach department indicates that the official account of the Faculty of Dentistry has a visualization of its histories of 35%.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is suggested that the accounts created in this research were part of the student preferences. This percentage is very high when compared to data indicating that on Instagram, small accounts with less than 5,000 followers achieve an average reach of 8.43% in stories (12). Only some entertainment accounts reach 85% of views, and certain sports accounts have the highest following: 90% (13) At the level of the UCR, the Faculty outreach department indicates that the official account of the Faculty of Dentistry has a visualization of its histories of 35%.…”
Section: Discussionmentioning
confidence: 92%
“…Responsiveness of a website is now an essential ability that brings new visitors to the website and retains existing ones (Vosylius & Lapin, 2015). Social media even highlight the trend (Kuchta & Stanková, 2019). Responsiveness has become a standard that is also followed by technology giants whose services represent significant sources of website traffic.…”
Section: Introductionmentioning
confidence: 99%
“…Instagram users can be found around us, especially young people, as a means of entertainment to relieve stress and fill empty time. Especially now, in an increasingly modern era, life is made more accessible by social media, one of which is Instagram (Putra et al, 2022). Sometimes, there are also many job vacancy hoaxes on Instagram.…”
Section: Introductionmentioning
confidence: 99%